Superficial angiomyxoma of the vulva: A case report and literature review (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Angiomyxomas are rare mesenchymal tumors. Aggressive angiomyxomas aredistinguished from superficial angiomyxomas by their propensity for local recurrence and metastaticpotential. Superficial angiomyxomas occur almost exclusively in women of reproductive age. Widesurgical resection is the treatment of choice.Case presentation: A 25-year-old para 1+1 presented with a mass on the vulva that had been increasingin size over one month. Examination revealed a mushroom-like, verrucous mass on the left labia majorawith a raw surface measuring approximately 4 cm in diameter with a 2-cm stalk. It was easily bleeding ontouch and slightly tender. Biopsies were taken, and histology revealed features of superficialangiomyxoma. The patient consented to wide excision of the vulval mass. The mass was excisedtogether with approximately 1.5 cm skin margin around it and a 2 cm depth of the underlying fatty base. Afinal histological diagnosis of superficial angiomyxoma was made. The patient was followed up for threemonths with no recurrence.Conclusion: Superficial angiomyxomas are rare benign tumors of the subcutaneous tissue that occuralmost exclusively in women of reproductive age. They present as slow-growing masses on the ear,trunk, and perineum. Wide surgical resection is the treatment of choice with adjuvant therapies, such asselective estrogen receptor modulators and gonadotropin hormone-releasing hormone agonists, alsoproving beneficial. Due to high rates of recurrence, long-term follow-up should be done for up to 15 yearsfollowing primary resection.